Non-native plant integration into plant-insect pollinator networks in urban parks - Laura Matas-Granados; Alejandro Trillo; Montserrat Vilà (PLoS ONE, 2026)
Pollination sustains biodiversity and ecosystem functioning, yet it is increasingly threatened by biological invasions. Non-native plants frequently integrate into plant-pollinator networks, generating both positive and negative effects on native plants. However, most current knowledge derives from static or short-term studies of communities invaded by a few species, offering limited understanding of plant-pollinator dynamics in systems where many non-native species coexist under favorable environmental conditions. Here, we examined plant-insect pollinator networks in urban green areas of a Mediterranean city as a model system to evaluate the role of non-native plants in structuring plant-pollinator networks over the course of one year. We compared native and non-native plants in terms of (i) species-level parameters (normalized degree, strength, specialization, contribution to nestedness, and module roles), (ii) modularity and co-flowering patterns, (iii) persistence of interactions, and (iv) beta-diversity metrics. Non-native plants showed greater specialization and among-module connectivity, whereas native species exhibited greater species strength and within-module connectivity. Native–non-native pairs within modules co-flowered more often, suggesting simultaneous interactions that may foster both competition and facilitation. In contrast, non-native–non-native pairs displayed asynchronous flowering, potentially sustaining shared pollinators over longer periods and mitigating competition. Despite these differences, both groups contributed similarly to temporal network connectivity, and interaction turnover was unaffected by the proportion of non-native species. Overall, these findings reveal that while native and non-native plants play distinct roles in structuring plant-pollinator networks, they do not differ in their contribution to maintaining temporal connectivity. Our study underscores the importance of incorporating temporal and multispecies approaches when assessing the ecological consequences of biological invasions.